Engaging People Who Inject Drugs Living With HIV in Antiretroviral Treatment and Medication for Opioid Use Disorder: Extended Follow-up of HIV Prevention Trials Network (HPTN) 074. (29th May 2021) - Lancaster, Kathryn E; Mollan, Katie R; Hanscom, Brett S; Shook-Sa, Bonnie E; Ha, Tran V; Dumchev, Kostyantyn; Djoerban, Zubairi; Rose, Scott M; Latkin, Carl A; Metzger, David S; Go, Vivian F; Dvoriak, Sergii; et al.
Abstract: Background: People who inject drugs (PWID) living with HIV experience inadequate access to antiretroviral treatment (ART) and medication for opioid use disorders (MOUD). HPTN 074 showed that an integrated intervention increased ART use and viral suppression over 52 weeks. To examine durability of ART, MOUD, and HIV viral suppression, participants could re-enroll for an extended follow-up period, during which standard-of-care (SOC) participants in need of support were offered the intervention. Methods: Participants were recruited from Ukraine, Indonesia and Vietnam and randomly allocated 3:1 to SOC or intervention. Eligibility criteria included: HIV-positive; active injection drug use; 18-60 years of age; ≥1 HIV-uninfected injection partner; and viral load ≥1, 000 copies/mL. Re-enrollment was offered to all available intervention and SOC arm participants, and SOC participants in need of support (off-ART or off-MOUD) were offered the intervention. Results: The intervention continuation group re-enrolled 89 participants, and from week 52 to 104, viral suppression (<40 copies/mL) declined from 41% to 29% (estimated 9.4% decrease per year, 95% CI -17.0%; -1.8%). The in need of support group re-enrolled 94 participants and had increased ART (re-enrollment: 55%, week 26: 69%) and MOUD (re-enrollment: 16%, week 26: 25%) use, and viral suppression (re-enrollment: 40%, week 26: 49%). Conclusions: Viral suppression declined in year 2 for those who initially received the HPTN 074 intervention and improved maintenance support is warranted. Viral suppression and MOUD increased among in need participants who received intervention during the study extension. Continued efforts are needed for widespread implementation of this scalable, integrated intervention. Abstract : HPTN 074 was an intervention for HIV and opioid use disorder treatment among people who inject drugs living with HIV. In the study extension, viral suppression declined for initial intervention group, yet viral suppression improved for those new to intervention.